Sanctorum Communio : Dietrich Bonhoeffer Works, Volume 1 - Bonhoeffer, Dietrich, 1906-1945 (Book collections on Project MUSE., 1998)
Now in an affordable paper edition, Sanctorum Communio is more readily usable for teaching and scholarship. The work, available in this series for the first time in its entirety in English, includes all material omitted from the original 1930 German publication. Bonhoeffer's doctoral dissertation sets out the theology of sociality that informed all his work, engaging social philosophy and sociology to interpret the church as ""Christ existing as church-community.